Sub-aperture beam-based adaptive beamforming for large dynamic arrays - Cox, H.; Hung Lai (2004 38th Asilomar Conference on Signals, Systems and Computers, 2004)
Large dynamically moving arrays present a significant challenge for adaptive beamforming (ABF). The combination of many array elements, large aperture and temporal instability results in a snapshot staved situation in which reduced degree-of-freedom approaches must be used. In some problems, beam-based approaches, in which conventional beamforming is used to provide a set of non-adaptive beams that are then adaptively combined, offer advantages both in performance and reduced computational complexity. A generalized beam-based ABF formulation is presented. This is then specialized to two dispirit cases that arise in underwater acoustics. The first is near-field focusing and interference rejection for a long line array. The second is azimuthal sidelobe and backlobe interference rejection for a large multi-line volumetric array that was discussed here last year (3). The physical constraints on these problems are discussed. Realistic large array simulations are used to show the effectiveness of the approach. The beam-based algorithms are shown to achieve excellent performance with low computational burden.